Enhancing efficiency of planar structure perovskite solar cells using Sn-doped TiO2 as electron transport layer at low temperature. (20th January 2018) - Cai, Qingbin; Zhang, Yiqiang; Liang, Chao; Li, Pengwei; Gu, Hao; Liu, Xiaotao; Wang, Jiefei; Shentu, Zhexian; Fan, Jiajie; Shao, Guosheng
Abstract: Sn-doped TiO2 films were successfully deposited by low-temperature solution method as electron transport layer (ETL), whose influence on the performance of perovskite solar cell (PSC) was investigated. In this work, X-ray photoelectron spectroscopy and X-ray diffraction revealed that Sn 4+ was successfully incorporated into the TiO2 lattice as an effective metal ion dopant without forming secondary phases. Compared with pristine TiO2, the Sn-doped TiO2 is more efficient for photogenerated electron extraction and transport, showing lower trap-state density and higher conductivity. Higher short-circuit current (Jsc ) is obtained due to the enhanced carrier transport velocity and improved charge collection efficiency, leading to a higher fill factor (FF) and better energy transfer efficiency. Our optimized planar solar cell using such a Sn-doped TiO2 ETL has achieved power conversion efficiency (PCE) of 17.2%, which was almost 29.3% higher than that of sample using the undoped TiO2 . To the best of our knowledge, this is the lowest processing temperature for Sn-dope TiO2 film at present, which provides an effective route towards flexible high-performance PSCs. Graphical abstract: Image 1 Highlights: Sn-doped TiO2 thin film can be grown via a facile low-temperature solution method. Sn-doped TiO2 film is more efficient for photogenerated electron extraction and transport. Through Sn-doping of TiO2, over 17.2% power conversion efficiency can be achieved by PSCs.